2020
DOI: 10.1007/s12063-020-00161-0
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the pick-up service quality scale of the buy-online-pick-up-in-store service

Abstract: Buy-Online-Pickup in Store (BOPS) service is a popular omnichannel retail initiative, intended to enhance the convenience of online customers. Focusing on the pickup (PU) stage of BOPS service, we develop a comprehensive scale (BOPS-PU-QUAL) for its quality perceived by customers. A multi-step scale development procedure involving one qualitative and two quantitative studies resulted in a scale consisting of 16 items under four dimensions. Service effectiveness is found to be the strongest influencer on qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 83 publications
(148 reference statements)
1
45
0
Order By: Relevance
“…Kim et al [16] found that hedonic motivation positively impacted consumers' behavioral intentions toward using BOPI. Other studies revealed that utilitarian value (e.g., save time, money, and effort) was the primary determinant of consumer selection BOPI method [94,95].…”
Section: Behavioral Responses and Moderating Effect Of Perceived Covid-19 Vulnerabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Kim et al [16] found that hedonic motivation positively impacted consumers' behavioral intentions toward using BOPI. Other studies revealed that utilitarian value (e.g., save time, money, and effort) was the primary determinant of consumer selection BOPI method [94,95].…”
Section: Behavioral Responses and Moderating Effect Of Perceived Covid-19 Vulnerabilitymentioning
confidence: 99%
“…According to Lee et al [94], PBC positively influenced consumers' intentions toward using BOPI because when an order was placed online for in-store pickup, consumers could pick up the order within a short time and check the quality of the product in person. This process makes consumers feel that they have control over the whole shopping process and they are able to reach their goals [94].…”
Section: Behavioral Responses and Moderating Effect Of Perceived Covid-19 Vulnerabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al. (2020) suggests that perceptions of service effectiveness and ease of use (i.e., buy online, pick‐up offline) satisfy the customer's retail experience (i.e., seek and feel enjoyment). Together, the findings explain the popular implication of the online shopping services into store‐based big‐box retailers with consumers who enjoy the service.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…The third stream concentrates on omnichannel retailing, some widely used omnichannel fulfillment options were explored in previous studies, such as the buy‐online‐and‐pick‐up‐in‐store (BOPS) (Gao & Su, 2017; Jin et al, 2018; Lee et al, 2020; MacCarthy et al, 2019; Wang et al, 2021; Xu et al, 2021); buy‐online‐and‐return‐to‐store (BORS) (Yan et al, 2020); reserve‐online‐pick‐up‐and‐pay‐in‐store (ROPS) (Zhang et al, 2018); ship‐to‐store (Gallino et al, 2017); ship‐from‐store (He et al, 2021; Li, 2020); showrooms (Li et al, 2019; Zhang et al, 2021); store return options (He et al, 2020; Nageswaran et al, 2020). Although omnichannel fulfillment options have been widely investigated in the retail industry, few studies have explored channel integration in the foodservice industry.…”
Section: Literature Reviewmentioning
confidence: 99%